Justice as relationality: socio-ecological justice in the context of anti-hydropower movements in Turkey - Yaka, Özge (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
By introducing a notion of socio-ecological justice, this article aims to deepen the relationship between environment and justice, which has already been firmly established by environmental justice movements and scholarship. Based on extensive fieldwork on local community struggles against small-scale run-of-river hydropower plants in Turkey, it expands the justice frame of environmental justice scholarship by going beyond the established conceptions of environmental justice as distribution – of environmental hazards and benefits, recognition and representation. Drawing on ethnographical fieldwork conducted in the East Black Sea region of Turkey, the article introduces the notion of socio-ecological justice to translate the relationality of the social and the ecological, of human life and non-human world, to the vocabulary of justice. It aims to extend the strictly humanist borders of social justice by maintaining that our intrinsic and intimate relations with the non-human world are an essential part of our well-being, and central to our needs to pursue a fair, decent life. It also seeks to contribute to the broader debate to facilitate a ‘progressive composition’ of a common, more-than-human world.